Repeated Colonization Between Arid and Seasonal Wet Habitats, Frequent Transition Among Substrate Preferences, and Chemical Diversity in Western Australian Xanthoparmelia Lichens - Autumn, Kendra; Barcenas-Peña, Alejandrina; Kish-Levine, Samantha; Huang, Jen-Pan; Lumbsch, H. Thorsten (Frontiers in Ecology and Evolution, 2020)
Arid soil habitats are challenging for sedentary and slow-growing lichens because the integrity of the substrate can easily be disturbed by natural forces, e.g., wind and flood. Yet, adaptation into such habitat types occurred multiple times in lichens that may be associated with specific morphological and ecological adaptations. We studied the genetic and chemical diversity of the lichen-forming fungal genus Xanthoparmelia in Western Australia, where it is abundant in both arid and temperate ecoregions occurring on both soil and rock substrates. We found frequent evolutionary transitions among substrate types and between arid and temperate habitats. However, specific chemical phenotypes were not associated with different habitat and substrate types, and the level of phenotypic (the composition of secondary metabolites) divergence was not correlated with the level of genetic divergence among taxa. The study closes by discussing the importance of arid soil habitats for evolutionary diversification in the hyperdiverse genus Xanthoparmelia.